EFSUMB Guidelines on Interventional Ultrasound (INVUS), Part VI – Ultrasound-Guided Vascular Interventions - Jenssen, C.; Brkljacic, B.; Hocke, M.; Ignee, A.; Piscaglia, F.; Radzina, M.; Sidhu, P. S.; Dietrich, C. F. (Ultraschall in der Medizin - European Journal of Ultrasound, 2016)
The sixth part of the Guidelines on Interventional Ultrasound produced under the auspices of the European Federation of Societies for Ultrasound in Medicine and Biology (EFSUMB) assesses the evidence for ultrasound guidance and assistance in vascular interventions. Based on convincing data, real-time sonographic guidance for central venous access is strongly recommended as a key safety measure. Systematic analysis of scientific literature shows that in difficult situations and special circumstances US guidance may also improve the efficacy and safety of peripheral venous and arterial access and endovascular interventions. Moreover, the recommendations of this guideline endorse the use of ultrasound to detect complications of vascular access and US-guided interventional treatment of arterial pseudoaneurysms.
Keywords: guideline; venous access; arterial access; endovascular interventions; ultrasound guidance; arterial pseudoaneurysm